Serum Bilirubin Is Inversely Associated with Increased Arterial Stiffness in Men with Pre-Hypertension but Not Normotension. - Yao-Hsien Huang; Yi-Ching Yang; Feng-Hwa Lu; Zih-Jie Sun; Jin-Shang Wu; Chih-Jen Chang (PLoS ONE, 2016)
OBJECTIVE:Serum bilirubin level has shown to be inversely associated with coronary atherosclerosis, and may serve as a protective biomarker of coronary artery disease. Serum bilirubin has also been shown to be negatively associated with brachial-ankle pulse wave velocity (baPWV) in men without a history of hypertension, and in men with hypertension. It is unknown whether such associations can be observed in the pre-hypertensive or normotensive population. This study thus aimed to investigate the relationship between serum bilirubin level and increased arterial stiffness in subjects with pre-hypertension and normotension for both genders. METHODS:A cross-sectional sample of 3,399 apparently healthy subjects undergoing a medical check-up at National Cheng Kung University Hospital was enrolled between October 2006 and August 2009, after excluding subjects with serum total bilirubin level greater than 20.52 μmol/L. Increased arterial stiffness was defined as baPWV of 1,400 cm/s or higher as the dichotomous variable and bilirubin as the continuous variable. RESULTS:Based on multiple linear regression analysis, serum bilirubin level was inversely associated with baPWV in non-hypertensive men (β = -0.066, p < 0.001) but not in non-hypertensive women. In addition, the inverse relationship between bilirubin level and baPWV was found statistically significant only in pre-hypertensive men (β = -0.110, p < 0.001). Multiple logistic regression analysis showed that serum bilirubin was inversely associated with increased arterial stiffness in men with pre-hypertension (odds ratio = 0.955, 95% confidence interval = 0.916-0.996, p < 0.05) but not normotension after adjustment for other confounding factors. However, the relationship between total bilirubin level and increased arterial stiffness did not reach statistical significance for female subjects with pre-hypertension and normotension. CONCLUSION:Serum bilirubin is inversely associated with increased arterial stiffness in men with pre-hypertension but not normotension. The association between bilirubin level and arterial stiffness was not found significant in women.